STRATEGI PEMASARAN DAN LEGALITAS PRODUK UMKM OBAT TRADISIONAL DI PEDESAAN - Zamalludin Sembiring; Saiful Bahri; Rian Novita Sari; Luthfia Suza; Nur Amin Lase; Bella Yuniana Suci Siregar; Aisyah Nurfadillah Lubis (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Traditional medicine MSMEs in rural areas have significant potential as economic drivers and preservers of local wisdom. However, limited marketing networks and incomplete legal compliance remain major obstacles for their development. This article aims to analyze relevant marketing strategies and the urgency of product legality for traditional medicine MSMEs, particularly in rural areas around Medan. The implementation method used a qualitative approach through community education, counseling, and MSME group consultations. Data were obtained from interviews, observations, and regulatory documents related to business legality. The results show that digital and community-based marketing strategies have proven effective in expanding market reach. Meanwhile, fulfilling legality requirements through BPOM distribution permits and halal certification is essential to increase consumer trust and access modern markets. The study concludes that combining innovative marketing strategies with strict legal compliance is the key to the sustainability of traditional medicine MSMEs in rural areas.